Influence of Isoflurane on Immediate-Early Gene Expression - Bunting, Kristopher M.; Nalloor, Rebecca I.; Vazdarjanova, Almira (Frontiers in Behavioral Neuroscience, 2016)
Background: Anterograde amnesia is a hallmark effect of volatile anesthetics. Isoflurane is known to affect both the translation and transcription of plasticity-associated genes required for normal memory formation in many brain regions. What is not known is whether isoflurane anesthesia prevents the initiation of transcription or whether it halts transcription already in progress. We tested the hypothesis that general anesthesia with isoflurane prevents learning-induced initiation of transcription of several memory-associated immediate-early genes (IEGs) correlated with amnesia; we also assessed whether it stops transcription initiated prior to anesthetic administration. Methods: Using a Tone Fear Conditioning paradigm, rats were trained to associate a tone with foot-shock. Animals received either no anesthesia, anesthesia immediately after training, or anesthesia before, during, and after training. Animals were either sacrificed after training or tested 24 hours later for memory. Using Cellular Compartment Analysis of Temporal Activity by Fluorescence in situ Hybridization (catFISH), we examined the percentage of neurons expressing the IEGs Arc/Arg3.1 and Zif268/Egr1/Ngfi-A/Krox-24 in the dorsal hippocampus, primary somatosensory cortex, and primary auditory cortex. Results: On a cellular level, isoflurane administered at high doses (general anesthesia) prevented initiation of transcription, but did not stop transcription of Arc and Zif268 mRNA initiated prior to anesthesia. On a behavioral level, the same level of isoflurane anesthesia produced anterograde amnesia for fear conditioning when administered before and during training, but did not produce retrograde amnesia when administered immediately after training. Conclusions: General anesthesia with isoflurane prevents initiation of learning-related transcription but does not stop ongoing transcription of two plasticity-related IEGs, Arc and Zif268, a pattern of disruption that parallels the effects of isoflurane on memory formation. Combined with published research on the effects of volatile anesthetics on memory in behaving animals, our data suggests that different levels of anesthesia affect memory via different mechanisms: general anesthesia prevents elevation of mRNA levels of Arc and Zif268 which are necessary for normal memory formation, while anesthesia at lower doses affects the strength of memory by affecting levels of plasticity-related proteins.